Antibiotic resistance status of helicobacter pylori strains isolated from initial eradication patients in Ningbo, China, from 2017 to 2021. Issue 5 (8th August 2022) - Shao, Yongfu; Lin, Yifan; Wang, Bojun; Miao, Min; Ye, Guoliang
Abstract: Background: Resistance of Helicobacter pylori ( H. pylori ) to antibiotics is an evolving and dynamic process. Presence of antibiotic resistance impacts the success rate of initial eradication strategies in the clinic. Aim: To improve the success rate of initial eradication therapy and explore new antibiotic regimens, a large sample‐based study utilizing antimicrobial susceptibility testing was performed. A total of 2508 H. pylori strains from patients subjected to initial eradication therapy were isolated, cultured, and tested for drug susceptibility from 2017 to 2021. The minimal inhibitory concentration (MIC) was recorded. H. pylori susceptibility profiles and its change trends from initial eradication patients were analyzed. The relationships between drug resistance, year of sample collection, age, and sex of patients were analyzed. Results: The overall resistance rates were as follows: amoxicillin (9.25%), clarithromycin (38.48%), levofloxacin (42.86%), furazolidone (11.28%), doxycycline (8.56%), rifampicin (10.81%), tinidazole (74.32%), gatifloxacin (61.71%), tetracycline (0%), metronidazole (78.71%), ornidazole (97.87%), and fosfomycin (31.67%). Only 38.04% of the strains were pansusceptible to amoxicillin, clarithromycin, levofloxacin, and furazolidone, followed by those of mono resistance (29.90%), double resistance (24.96%), triple resistance (6.34%), and quadruple resistance (0.76%). Significant differences in the resistance rate and MIC were also observed in different age and sex groups. Time of collection and patient age and sex were associated with the distribution of antibiotic resistance. Conclusion: With the increasing resistance rate and multiple resistance of H. pylori to commonly used antibiotics, drug susceptibility testing is imperative to permit individualized therapy, and a regimen containing the combination of amoxicillin, furazolidone, tetracycline, doxycycline, or rifampicin is reasonable for initial empirical eradication therapy.